INHIBITION OF MYCOFLORA AND ZEARALENONE ON RICE BY SELECTED ESSENTIAL OILS - HASAN, H. A. H. (Biological Sciences - PJSIR, 2022)
Effect of natural products viz, anise, cinnamon, clove, marjoram and peppermint on the inhibition of mycoflora and zearalenone production on rice grains was studied. Population of fungi significantly reduced by spice oils used as O.J, 0.3, 0.5 and 1.0% and completely inhibited at 1% cinnamon. Fusarium graminearum grown in sterilized liquid medium and on cooked and uncooked rice grains showed complete inhibition of zearalenone production where anise, cinnamon and clove as 0.5% were used.Marjoram and peppermint oils as 0.5% on uncooked and as I% on cooked rice showed inhibitory effects. In rice extract liquid medium, cinnamon and anise oils had most pronounced effect and significantly reduced zearalenone production at 0.02 and 0.05% respectively.